The effect of group support psychotherapy on adherence to anti-retroviral therapy and viral suppression among HIV positive young people: Study protocol for a pilot randomized controlled trial - Nakimuli-Mpungu, Etheldreda; Wamala, Kizito; Nalugya, Joyce Sserunjoji; Nakanyike, Caroline; Iya, Jane; Bakeera Kitaka, Sabrina; Diana Namuli, Justine; Akimana, Benedict; Nachega, Jean B.; Mills, Edward J.; Seggane, Musisi (Frontiers in Health Services, 2023)
Background: Several studies have demonstrated an association between psychological risk factors and HIV disease progression. However, there is limited information on the use of psychological interventions to improve HIV treatment outcomes in young people living with HIV. Objective: This pilot trial aims to evaluate the feasibility, acceptability and preliminary effectiveness of group support psychotherapy in improving adherence to antiretroviral therapy and viral suppression in young people living with HIV in Uganda. Methods: We recruited 120 young people with HIV, aged 10-18 years, who had non-viral suppression 6 months after initiating first-line antiretroviral therapy (ART) from community-based HIV clinics in Kitgum district, northern Uganda. Participants were randomly assigned to receive GSP plus IAC (N=60) or IAC alone (N=60). Primary outcomes will be indicators of feasibility and acceptability as well as preliminary effectiveness of GSP in improving ART adherence and viral suppression analyzed by intention to treat using cluster-adjusted t-tests and permutation tests. Secondary outcomes will be measures of depression, anxiety, and cost-effectiveness. Results: The trial has been approved by the Makerere College of Health Sciences School of Health Sciences Research Ethics Committee, and the Uganda National Council of Science and Technology. Recruitment began in June 2021 and 120 young people living with HIV with their adult caregivers have been recruited to the trial. An analysis of baseline and 6-month data is in progress. The results of this trial will not only be presented at national and international conferences but also submitted for publication in peer-reviewed journals and as a report to the funding agencies. Conclusions: This pilot trial will provide critical evidence to support the ongoing mental health integration into routine HIV care in Uganda. Trial Registration: Pan African Clinical Trials Registry (PACTR): 201608001738234